Metabolic changes after surgical fat removal: A dose–response meta-analysis. (January 2023) - Badran, Saif; Habib, Abdella M.; Aljassem, Ghanem; Musa, Omran A.H.; Clark, Justin; Hamdi, Moustapha; Abou-Samra, Abdul-Badi; Glass, Graeme E.; Doi, Suhail A.
Abstract: Background: Bariatric surgery averts obesity-induced insulin resistance and the metabolic syndrome. By contrast, surgical fat removal is considered merely an esthetic endeavor. The aim of this article was to establish whether surgical fat removal, similar to bariatric surgery, exerts measurable, lasting metabolic benefits. Methods: PubMed, Embase, and Scopus were searched using the Polyglot Search Translator to find studies examining quantitative expression of metabolic markers. Quality assessment was done using the MethodologicAl STandard for Epidemiological Research scale. The robust-error meta-regression model was employed for this synthesis. Results: Twenty-two studies with 493 participants were included. Insulin sensitivity improved gradually with a maximum reduction in fasting insulin and homeostatic model assessment for insulin resistance of 17 pmol/L and 1 point, respectively, at postoperative day 180. Peak metabolic benefits manifest as a reduction of 2 units in body mass index, 3 kg of fat mass, 5 cm of waist circumference, 15 µg/L of serum leptin, 0.75 pg/ml of tumor necrosis factor-alpha, 0.25 mmol/L of total cholesterol, and 3.5 mmHg of systolic and diastolic blood pressure that were observed at day 50 but were followed by a return to preoperative levels by day 180. Serum high-density lipoproteins peaked at 50 days post-surgery before falling below the baseline. No significant changes were observed in lean body mass, serum adiponectin, resistin, interleukin-6, C-reactive protein, triglyceride, low-density lipoproteins, free fatty acids, and fasting blood glucose. Conclusion: Surgical fat removal exerts several metabolic benefits in the short term, but only improvements in insulin sensitivity last beyond 6 months.